2011
DOI: 10.1248/cpb.59.57
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Pseudo-Crystalline Transformation from Form I to Form II of Thiamine Hydrochloride (Vitamin B1)

Abstract: There are three types of pseudo-polycrystalline forms of thiamine hydrochloride (vitamin B 1 ): form I (monohydrate); form II (hemihydrate); and form III (anhydrate). These crystal structures were elucidated using single-crystal X-ray structural analysis, form I by Kraut and Reed in 1962, 1) form II by Watanabe et al. in 1979, 2) and form III by Te et al. in 2003. 3) Since then, there have been various reports on the physiochemical properties of these pseudo-polycrystalline forms. 4,5) The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Under the condition of constant temperature, damping air [5], mixing air flows of varying humidity [10]- [12], and using saturated salt solutions [13]- [16] can achieve the environments with a RH that will satisfy the requirements of sensor testing. Depending on several automatic control systems, the methods of damping air and mixing air flows to obtain an environment with a particular RH make a test system sophisticated and expensive.…”
Section: A Humidity Generatormentioning
confidence: 99%
“…Under the condition of constant temperature, damping air [5], mixing air flows of varying humidity [10]- [12], and using saturated salt solutions [13]- [16] can achieve the environments with a RH that will satisfy the requirements of sensor testing. Depending on several automatic control systems, the methods of damping air and mixing air flows to obtain an environment with a particular RH make a test system sophisticated and expensive.…”
Section: A Humidity Generatormentioning
confidence: 99%
“…The effect of temperature and relative humidity on the transition of form-I to form-II has been studied and the kinetics associated with transformation of the bulk drug substance was reported as 121-155 kJ/mol at relative humidities of 70%-90%. 146 The thermally induced dehydration processes associated with various thiamine hydrochloride hydrates have been reported in a two-part study. 147,148 It was concluded that the cooperative deformation of thiamine molecules that takes place during the dehydration process served to facilitate a nondisruptive loss of water from the lattice, which was explained in terms of a "continuous and unified" dehydration model.…”
Section: Phase Transformations Of Polymorphs and Solvatomorphsmentioning
confidence: 99%
“…This causes some of the NSH crystals to dissolve or deliquesce. Recrystallisation of the HH crystals then occur as they have a lower water solubility (Masuda et al, 2011). Even though the HH is exceptionally stable, it has lower aqueous solubility and has poorer powder flow characteristics (Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%